(untitled) (Revista Cientifica Ingenio Magno, 2021)
Electricity generation through biomass gasification can be a viable and environment-friendly alternative. In this work, residual biomasses from corn, coconut, and coffee were proposed based on the mapping of information in databases, as the immediate and elementary analysis, simulations were performed using Computational Fluid Dynamics tools to determine the fractions molars of the synthesis gas generated from the gasification of each residue. The calorific value was calculated and its performance evaluated when supplied as fuel for a 15kWe engine-generator specified from data obtained in the literature, providing stable electricity from the burning of syngas. With a constant supply of 18 kg/hour, it would be necessary to gasify residues of 6.5 hectares of corn or 17 hectares of coconut, or 124 hectares of coffee. In these conditions, with continuous feeding, 24 hours/day, there is the generation of 10,800 kWh in one month, enough to feed an unconnected community of 67 residences, which proves the feasibility of the research for this application.